1982
DOI: 10.1159/000112709
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of High Affinity Neuronal Recognition Sites for <sup>3</sup>H-5-HT in Rat Brain

Abstract: The postnatal development of 3H-5-HT specific binding sites has been studied in rat brain. Experimental conditions allowed the characterization of the class of sites corresponding to the synaptosomal receptor for 5-HT. The related affinity constant and maximal binding were measured at various ages after birth. During the second week after birth, the serotonin receptor system developed explosively, the maximal number of sites increasing from a nonsignificant value to that observed in adult rats. Lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Accumulated evidence suggests that during embryogenesis 5-HT acts as a differentiation signal for serotonergic neurons and their target cells by activating appropriate receptors (Azmitia, 2001;Gromová et al, 1983;Haydon et al, 1987;Lauder and Krebs, 1978). We know already that 5-HT is released from developing serotonergic neurons (Mercado et al, 1998) and that it interacts with 5-HT receptors modulating their expression (Fillion et al, 1982;Mercado and Hernandez-R, 1992;Mercado et al, 1998;Morilak and Ciaranello, 1993;Whitaker-Azmitia, 1991); some studies have identified various 5-HT receptor subtypes during mid-gestation, including 5-HT 1A , 5-HT 2A, 5-HT 2B , and 5-HT 2C , which could mediate the effects of serotonin during brain development (Bolaños et al, 1997;Davidson and Stamford, 1995;Duncan et al, 2000;Morilak and Ciaranello, 1993;Nebigil et al, 2001;O'Connor and Kruk, 1992), as observed in this study for 5-HT 1A and 5-HT 1B receptors. The presence of 5-HT 1A in axonal growth cones suggest their involvement in the signaling processes related to axogenesis and synaptogenesis (Bar et al, 1991;Lauder et al, 2000;Mercado et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accumulated evidence suggests that during embryogenesis 5-HT acts as a differentiation signal for serotonergic neurons and their target cells by activating appropriate receptors (Azmitia, 2001;Gromová et al, 1983;Haydon et al, 1987;Lauder and Krebs, 1978). We know already that 5-HT is released from developing serotonergic neurons (Mercado et al, 1998) and that it interacts with 5-HT receptors modulating their expression (Fillion et al, 1982;Mercado and Hernandez-R, 1992;Mercado et al, 1998;Morilak and Ciaranello, 1993;Whitaker-Azmitia, 1991); some studies have identified various 5-HT receptor subtypes during mid-gestation, including 5-HT 1A , 5-HT 2A, 5-HT 2B , and 5-HT 2C , which could mediate the effects of serotonin during brain development (Bolaños et al, 1997;Davidson and Stamford, 1995;Duncan et al, 2000;Morilak and Ciaranello, 1993;Nebigil et al, 2001;O'Connor and Kruk, 1992), as observed in this study for 5-HT 1A and 5-HT 1B receptors. The presence of 5-HT 1A in axonal growth cones suggest their involvement in the signaling processes related to axogenesis and synaptogenesis (Bar et al, 1991;Lauder et al, 2000;Mercado et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Membranes from homogenates were obtained as previously described by Fillion et al (1982). Enriched fractions with neurons were isolated from brainstem according to Rose (1967).…”
Section: Biochemical Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…A good model to study the effect of ELF on cells under intense transformation is the embryonic and the early postnatal growth period (Cameron et al, 1993;Yang et al, 1992;Ho et al, 1992;Moses and Martin, 1992;Martin, 1992;Wiley et al, 1992;Husskoen and Koulainen, 1993;Frolen et al, 1993;Sakamoto et al, 1993). In the rat brain serotonin synapses are under intense and continuous growth during the first 2 weeks of postnatal development and serotonin (5-HT) content parallel this increase (Fillion et al, 1982;Zifa et al, 1980;Hernández et al, 1984). This preliminary report describes the effect of ELF on the 5-HT content of the cerebral cortex of normal growing offsprings of Wistar rats exposed during pregnancy to ELF.…”
Section: Introductionmentioning
confidence: 99%